Analysis of Non-Halal Drug Use in the Perspective of Maqashid Syariah - Umi Kalsum Hehanussa (Jurnal Ilmiah Ekonomi Islam, 2022)
Indonesia is one of the largest island countries and the largest Muslim population in the world. This is related to the consumption of pharmaceutical supplies, especially the consumption of drugs. The use of drugs to improve the quality of health not only ensures safety, quality, and efficacy but also must be available halal guarantees on the product. This research aims to find out how the study of sharia maqashid related to the use of non-halal drugs. This research method uses this type of reseach library research with data collection methods obtained from various sources of articles and journals reviewed. The results showed that the use of non-halal drugs are drugs that are not in accordance with the provisions of Islamic sharia, whose way of manufacture and materials are not in accordance with Islamic sharia, and are not recommended for consumption by Muslims. In terms of Maqashid al-Syariah, it is very clear that the use of such non-halal drugs can be used with the consideration that maintaining the soul to avoid deadly diseases falls into the level of dharuriyyah / primer.